Factor influence customer intention to purchase house: case study in Wawasan Intact Properties / Norhidayah Jaafar - Jaafar, Norhidayah (2015)
Explaining human behavior is very important to determine the factor that influences the customer to make any decision to purchase something. By following the study of behavior, this study aim to determine the effect of attitude, subjective norms, perceived behavior control and location that influence the customer intention to purchase house. The theoretical of the study to examines the relationship of the customer intention to purchase the house with their attitude, subjective norms and perceived behavior control. The answer to the stated research questions were obtained through the questionnaires which were hand the client of Wawasan Intact Properties that intend to buy the house. This study involve 100 customers or respondents that participate to answer the questionnaire given, using the meth of multiple linear regression for data analysis, it was found that the perceived behavior control have a positive significant relationship with the intention of customer to purchase the house.